Teknik Penanganan Kendali Hewan Sesuai Kaidah Kesejahteraan Hewan Meningkatkan Akurasi Pengukuran Profil Hemodinamika Tikus Laboratorium - Darusman, Huda Shalahudin; Nugroho, Setyo Widi; Munggaran, Fauzi Abdurrahman; Sajuthi, Dondin (Jurnal Veteriner; Vol 19 No 2 (2018), 2018)
Chronic discomfort potentially occurred during a hemodynamic measurements in a rat-tail blood pressure chamber due to the animal is restrained in restricted space for a long period – it took 10 repetitions each at approximately 1.5 minutes for a session of hemodynamic measure. Procedures related to the animal welfare methods are required to improve the accuracy of the measurement which would altered from the discomfort to comfort state of the animal. Welfare procedures are represented by humane handling and habituation of the subject (rats) to the operator and the hemodynamic apparatus. Seven rats were subjected in this study and measured for hemodynamic value in three times point: before (T0), after humane handling (T1) and after human handling and habituation to the measurement apparatus (T2), respectively. Six out of seven subjects showed a significant lowering deviation for all variables of hemodynamic measurements, and that deviation followed by a declining trend from T0 to T2, i.e T0>T1>T2. The results indicated that welfare-based approach would benefit the animals from feeling discomfort and yet improving the accuracy and quality of the outcomes.